Measurement of Stopping Power, Residual Range and Equivalent Dose Rate of α- Particles in Polymers PP and PE - Ali KH. Hussain; Laith R. Mohammed; Ahmed K. Mheemeed (College of Education for Pure Sciences, 2009)
Abstract The stopping power of α-particles of initial energy 7.69 MeV (emitted from 214Po source) have been measured in the polyethylene(PE) and polypropylene(PP) using surface barrier detector technique and compared with calculated value by SRIM-2003 program. The deviations of the measured data from SRIM's results in PE and PP films are approximately about 0-7% and 0-11%. An empirical formulae between the stopping power and energy have been found. The residual energy, the residual range and the equivalent dose rate also calculated.